PEMBERDAYAAN DAN PELATIHAN PEMBUATAN HANTARAN PADA IBU-IBU PKK di DESA BANDUNGSARI KECAMATAN SUKODADI LAMONGAN - Khofifah Indar Parawansyah; Aqidatun Nisa’il Afrilia; Khafidhoh Nurul Aini; Abdur Rohim (LPPM Universitas Islam Darul 'Ulum Lamongan, 2024)
Many housewives who have spare time but do not work due to a lack of knowledge and skills. Therefore, the existence of training attended by PKK mothers in Dusun Bandung, Bandungsari Village, Sukodadi District, Lamongan Regency, East Java, can increase knowledge and skills to fill leisure time, thus enabling them to open hantaran-making services as a side business. The training activity method applies four stages which include: the first stage is a survey using literature study, interviews, and direct observation methods; the second stage is material presentation using direct learning methods or lectures and Q&A sessions; the third stage is training with direct practice methods; and the fourth stage is mentoring with direct observation methods. Based on the final scores obtained, which are 92% for enthusiasm, 88% for knowledge, and 90% for skills aspects, it can be concluded that overall this training is considered successful. Participants were enthusiastic in attending the training, understanding the presented material, and able to skillfully practice the training material. This training received positive responses, so it should be further developed, and there needs to be organized follow-up activities.